Advances in marine biology. - Lesser, Michael (Advances in marine biology., 2010)
Advances in Marine Biology has been providing in-depth and up-to-date reviews on all aspects of Marine Biology since 1963 -- over 40 years of outstanding coverage! The series is well-known for both its excellence of reviews and editing. The serial publishes in-depth and up-to-date content on a wide range of topics which will appeal to postgraduates and researchers in marine biology, fisheries science, ecology, zoology, and biological oceanography. * Rated "Number 1" in the highly competitive category of Marine & Freshwater Biology by ISI in the 2000 ISI journals citation report * Maintains an Impact Factor of 3.37, the highest in the field * Series features over 35 years of coverage of the research